Ultrafast manipulation of topologically enhanced surface transport driven by mid-infrared and terahertz pulses in Bi2Se3 - L. Luo (Nature Portfolio, 2019)
It remains challenging on how to selectively control terahertz conductivity at surface from the bulk contribution in topological insulators. Here, Luo et al. discover and manipulate topologically enhanced surface transport due to helical spin structure using mid-infrared and terahertz ultrafast photoexcitations.